Serum sclerostin levels associated with lumbar spine bone mineral density and bone turnover markers in patients with postmenopausal osteoporosis - XU, Xiao-juan; SHEN, Lin; YANG, Yan-ping; LU, Fu-rong; ZHU, Rui; SHUAI, Bo; LI, Cheng-gang; WU, Man-xiang (Chinese medical journal, 2013)
Background Sclerostin, expressed exclusively by osteocytes, is a negative regulator of bone formation. To gain insights into the action of sclerostin in postmenopausal osteoporosis, we evaluated serum sclerostin levels in postmenopausal women and investigated its possible associations with bone turnover markers in patients with postmenopausal osteoporosis. Methods We detected serum sclerostin, and measured lumbar spine bone mineral density in 650 Chinese postmenopausal women. We also assessed serum levels of 13-isomerized C-terminal crosslinking of type I collagen, intact N-terminal propeptide of type I collagen, N-mid fragment of osteocalcin, 25-hydroxyvitamin D, and estradiol. Results Serum sclerostin levels were lower in postmenopausal osteoporotic women compared with non-osteoporotic postmenopausal women （（38.79＋7.43） vs. （52.86＋6.69） pmol/L, P 〈0.001）. Serum sclerostin was positively correlated with lumbar spine bone mineral density （r=0.391, P 〈0.001） and weakly negatively correlated with [3-isomerized C-terminal crosslinking of type I collagen, intact N-terminal propeptide of type I collagen, N-mid fragment of osteocalcin （t= -0.225, P 〈0.001; r= -0.091, P=0.046; r= -0.108, P=0.018; respectively） in postmenopausal osteoporosis. There was no significant association of serum sclerostin with age, body mass index, 25-hydroxyvitamin D, and estradiol （r= -0.004, P=0.926; r=0.067, P=0.143; r=0.063, P=0.165; r= -0.045, P=0.324; respectively）.Conclusion Sclerostin may be involved in the pathogenesis of postmenopausal osteoporosis and may play a role in bone turnover.